2013
DOI: 10.1109/lpt.2013.2279502
|View full text |Cite
|
Sign up to set email alerts
|

Light Extraction Enhancement of GaN LEDs by Hybrid ZnO Micro-Cylinders and Nanorods Array

Abstract: A hybrid patterned ZnO micro-cylinders and nanorods array (MCNR) was fabricated to improve the light extraction efficiency for high brightness GaN-based light-emitting diodes (LEDs). The light extraction efficiency of the LEDs with the ZnO MCNR is increased by 86.4% compared with conventional planar LEDs. LEDs with ZnO MCNR have greater light extraction efficiency than those only with ZnO micro-cylinders or ZnO nanorods array. The optical-electrical characteristics and far-field radiation patterns are measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…ZnO nanostructures can be used as gradient refractive index layer because the refractive index of ZnO (n = 2.0) is between GaN (n = 2.5) and air (n = 1). Until now, researchers found that doping ZnO, especially with special nanostructures, into GaN-based blue LEDs was able to improve the light extraction [25][26][27][28][29]. Yin et al [26] applied a hybrid patterned ZnO micro-cylinders and nanorods array on the surface of LED chip to improve the light extraction efficiency for GaN-LEDs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ZnO nanostructures can be used as gradient refractive index layer because the refractive index of ZnO (n = 2.0) is between GaN (n = 2.5) and air (n = 1). Until now, researchers found that doping ZnO, especially with special nanostructures, into GaN-based blue LEDs was able to improve the light extraction [25][26][27][28][29]. Yin et al [26] applied a hybrid patterned ZnO micro-cylinders and nanorods array on the surface of LED chip to improve the light extraction efficiency for GaN-LEDs.…”
Section: Introductionmentioning
confidence: 99%
“…Until now, researchers found that doping ZnO, especially with special nanostructures, into GaN-based blue LEDs was able to improve the light extraction [25][26][27][28][29]. Yin et al [26] applied a hybrid patterned ZnO micro-cylinders and nanorods array on the surface of LED chip to improve the light extraction efficiency for GaN-LEDs. Yin et al [28] demonstrated a remarkable enhancement of light extraction efficiency in GaN based blue LEDs with rough beveled ZnO nanocone arrays grown on the planar ITO layer.…”
Section: Introductionmentioning
confidence: 99%
“…GaN-based LED chips were fabricated by sequentially growing undoped GaN (u-GaN, 2 μm), n-GaN (2 μm), five periods of InGaN/GaN multiple quantum wells (MQWs), p-GaN (250 nm), indium tin oxide (200 nm), and p- and n-type Cr/Au electrodes on c-plane sapphire substrates (400 μm), using a metal–organic chemical vapor deposition (MOCVD) process. The details of the LED-fabrication process can be found elsewhere. , The fabricated LED chips (set A) and silica glasses (set B) were used as substrates in equal experimental condition for further treatment.…”
Section: Experimental Sectionmentioning
confidence: 99%
“…To increase the LEE of LEDs, several approaches had focused on fabricating micro-/nanostructures either inside or outside the LEDs [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. For example, roughed GaN surface [3][4][5][6][7], roughed sapphire substrate [8,9], roughed indium tin oxide (ITO) surface [10][11][12], and grown ZnO micro-/nanostructures [13][14][15] have been implemented in LEDs. The common nanoscale patterning techniques, such as electron-beam lithography [16], nanoimprint lithography [17], holographic lithography [18], hydrothermally method [19], and nanosphere lithography (NSL) [20], are used to obtain nanoscale surface textures.…”
Section: Introductionmentioning
confidence: 99%